Albitization of granitic rocks: The mechanism of replacement of oligoclase by albite - Engvik, A.; Putnis, Andrew; Fitz Gerald, J.; Austrheim, H. (Mineralogical Association of Canada, 2008)
Large-scale metasomatic albitization in the albitite terranes of the Bamble sector of southeastern Norway has affected both mafic and granitic lithologies. In partially metasomatized tonalite, the albitization fronts advance normal to fractures and can be recognized in the field by a distinct reddening of the rock in which original plagioclase crystals are replaced by albite. To determine the mechanism of albitization within single crystals of Ca-bearing plagioclase (oligoclase: An21-23), intragranular replacement interfaces have been studied by electron-probe micro-analysis, scanning (SEM) and transmission electron microscopy (TEM). The albite replacement-product (An2-5) has micrometric pores observable by SEM, as well as nanopores imaged by TEM. The albite contains fine-grained white mica commonly associated with the pores, as well as precipitates of hematite. The interface between oligoclase and albite is sharp, with corresponding compositional gradients across no more than tens of nanometers, and the crystallographic orientations of oligoclase and albite are coincident within less than a degree. These are all characteristic features of an interface-coupled dissolution-reprecipitation mechanism of replacement which, in combination with fracturing, is responsible for the fluid infiltration and the mineral-replacement process.